The impact of coffee on human health - Aleksandra Chałupnik; Aleksandra Borkowska; Anna Sobstyl; Zuzanna Chilimoniuk; Maciej Dobosz; Paulina Sobolewska; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2019)
Introduction: Coffee is one of the most popular beverages in the world. It contains lots of biologically active ingredients. These compounds not only have aromatic properties, but many of them also have antioxidant, hepatoprotective, anti-inflammatory, antimicrobial, antiviral and relaxing smooth muscle properties. The aim of the study: The purpose of the study is to collect and review scientific publications about the impact of coffee on health. Material and method: The paper uses standard criteria as the research method. Additionally, during the literature review on PubMed and Google Scholar platforms, keywords such as coffee, caffeine, health, impact were used. Description of the state of knowledge: Numerous studies suggest that coffee impact on the long-term functioning of the organism is negligible and is associated with the consumption of coffee for a longer period of time. Chlorogenic acid, caffeine and trigoneline are primarily responsible for the positive effect. They have a hypoglycemic, bactericidal and antioxidant effect. Diterpenes, such as kahweol and cafestol may have negative influence on health. Research also suggests that coffee can reduce the risk of Parkinson's disease and type 2 diabetes. Summary: The results show that coffee ingredients can have both positive and negative effects on health. However, before these observations can be used to create nutritional advice, further research is needed. They will allow a better understanding of the mechanisms of action of the compounds responsible for reduced risk of diabetes mellitus or Parkinson's disease. Keywords: coffee, caffeine, health, cardiovascular